Waterproofing topsoil stockpiles minimizes viability decline in the soil seed bank in an arid environment - Golos, P.; Dixon, Kingsley (Blackwell Science Inc., 2014)
Topsoil is a valuable resource for revegetation of mine sites as it contains seeds of plant species indigenous to the local environment. As mine site restoration is undertaken after the completion of mining, it is a common practice to stockpile topsoil in preparation for restoration activities. While many studies have found a decrease in seedling emergence with increasing stockpile age in temperate regions around the world, a few examine the effect of stockpile age on topsoil seed bank and seedling recruitment in arid environments. Seed longevity is promoted under dry conditions whereas viability loss is increased under warm and moist conditions. Here in a study in Australia's Great Sandy Desert, the effect of topsoil storage age and method of storing topsoil (under-cover and exposed) on seedling recruitment was examined for a major gold mining site. There was a trend for lower seedling emergence (68% lower) and species richness (30% lower) from topsoil stored for 2 years than from topsoil direct returned and topsoil stored for 1 year. Seedling emergence from topsoil stockpiled for 2 years was more than 3.5-fold higher from covered topsoil stockpiles than uncovered topsoil stockpiles. For two ecologically dominant species, after 2 years of storage, seedling emergence of the grass Triodia basedowii was 13% of direct returned topsoil and seedling emergence of the shrub Acacia stellaticeps was 68% of direct returned topsoil. The implication of the decline in seedling emergence from topsoil stockpiling on mine site revegetation in a biodiverse arid region is discussed.